STRATEGI PONDOK PESANTREN DALAM MENCEGAH PAHAM RADIKALISME AGAMA (STUDI KASUS PONDOK PESANTREN UMMUL QUROK KLEGO BOYOLALI) - Abdulloh Al-Al Haris Dzulfirki; Fauzi Muharom (STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
Islamic boarding schools play an independent role in exploring the potential of the surrounding community to improve the quality of religion. This is because there are so many problems of the people of this era, especially in understanding religious ideology. The rise of understanding Radikaslime Pancasila which gives the impact of confusion of thinking for the community, especially students in understanding religion. This article focuses on the strategy of the Ummul Qurok Islamic boarding school Klego Boyolali in preventing religious radicalism against its students. Descriptive qualitative research approach with interviews and observations as well as interactive analysis. The results of the study that universal and contextual understanding of religion, namely understanding the text of the Qur'an and hadith contextually adapted to the times, cannot be separated from knowing asbabul al-nuzul or asbabul wurud. The strategic strategies of the Ummul Qurok Klego Boyolali Islamic boarding school include religiosity, namely increasing the religiosity of the students, both in the relationship with God and with human relations which are contained in Honesty, Totokromo (courtesy) and Rumongso (Feelings). The ideology of pesantren in the field of faith, the values of the soul of the pesantren are sincerity, simplicity, independence, ukhuwah Islamiyah and freedom. Cadreization is in order to avoid and controversy from outsiders who are not in line with the khottoh of the cottage. Social, namely to equip students when they enter the community